YOUNG INDONESIAN STUDENTS’ LEARNING STYLE AND STRATEGIES IN ACQUIRING ENGLISH AS SECOND LANGUAGE - Pratama, Erik Yuda (ENGLISH JOURNAL, 2016)
Learning strategies and style are intentionally used and consciously controlled by the learner. Learning strategies and style can also enable students to become more independent, autonomous, and lifelong learners. This qualitative study investigates some styles and strategies used by Indonesian learners who are learning English as their second language. The findings from this study show that some Young Indonesian learners link social strategy to cognitive strategy to learn English.